2021
DOI: 10.3390/met11071072
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Creep Properties of Cr-Si Alloys at 980 °C in Air—Influence of Ge and Mo Addition

Abstract: The tensile creep behavior of Cr-Si alloys with Cr ≥ 91 at.% was investigated in air at 980 °C with a constant load of 50–100 MPa. Additionally, the influence of substitutional alloying additions of 2 at.% Ge and Mo, leading to ternary alloys was studied. The addition of Ge or Mo results in an improvement in creep strength, with the highest strength achieved with addition of Mo. For longer creep exposure times a strong effect is observed, because of severe nitrogen uptake from the air, depending on alloy compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Petra Pfizenmaier et al [12] reported the tensile creep behavior of a binary alloy Cr 91 Si 9 and two ternary alloys, Cr 91 Si 7 Ge 2 and Cr 91 Si 7 Mo 2, in air at 980 • C. The tests were conducted under constant stress conditions of 50, 75, and 100 MPa. The substitution of Si with 2 at.% Ge or Mo considerably improved the creep resistance, with the highest resistance achieved by the alloy with Mo.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Petra Pfizenmaier et al [12] reported the tensile creep behavior of a binary alloy Cr 91 Si 9 and two ternary alloys, Cr 91 Si 7 Ge 2 and Cr 91 Si 7 Mo 2, in air at 980 • C. The tests were conducted under constant stress conditions of 50, 75, and 100 MPa. The substitution of Si with 2 at.% Ge or Mo considerably improved the creep resistance, with the highest resistance achieved by the alloy with Mo.…”
Section: Data Availability Statementmentioning
confidence: 99%